Cycling transport in the urban environment: synthesis of knowledge in the period 1990-2019 (Research, Society and Development, 2021)
Cycling use in cities has grown around the world as a result of sustainable urban mobility policies. This article aims to analyze trends and scientific research production on the expansion of bicycle use in the urban environment between 1990 and 2019. Bibliometrics was used aiming to analysing types of publications, access modality, publication languages, characteristics of articles, prominent journals, featured authors, keywords and countries of publications. A bibliometric map elaboration software was used for graphic visualization of simultaneous occurrence of keywords and bibliographic coupling between countries. 1559 publications were found in Scopus, covering 14 different types of documents. Most publications were written in English (96.34%) and had restricted access (75.37%). The Research Articles class stood out with the largest share of production (68.44%). There was a constant growth trend in the number of publications per year. The identified keywords are linked to the themes of Active Transport, Health and Urban Planning. The United States, Australia, Canada, Belgium and the United Kingdom were the countries that most stood out for having common references among the articles.